Implementasi Model Pembelajaran Blended Learning pada Mata Kuliah Pendidikan Agama Islam pada Era New Normal - Azis, Abd (Universitas Nahdlatul Ulama Pasuruan, 2022)
The implementation of lectures using the blended learning model is due to lectures that have not been maximally carried out face-to-face. To overcome this, lectures are carried out face-to-face and online, which is called the blended learning model. The research method uses descriptive qualitative, the research instrument uses observation and questionnaires. Sources of data in this study were lecturers of PAI courses and 1st semester IT students in class A totaling 27 and B totaling 29 who took PAI courses in the 2021/2022 academic year. The result of the research is that the implementation of Blended learning in the lecture process is carried out by combining face-to-face learning using active learning strategies such as discussion and role playing and online learning by utilizing the Google Meet and Google Classroom platforms. Student perceptions related to the implementation of blended learning are a) students define e-learning as online learning, using the internet, and learning using digital technology and as a tool for distance learning. b) students understand the blended learning model, namely lectures that are carried out in a mixture, sometimes online and offline. c) The type of platform used in implementing blended learning is google classroom. d) Students' opinions related to the benefits of blended learning are 31 students (56.4%) stating they are helpful in learning, e) Student opinions related to the obstacles faced are the lack of smooth internet access, dependence on the internet and electronic media and the need for adequate infrastructure. adequate, such as cellphones, laptops and so on. Keywords: Blended learning, PAI, New Normal